Health Worker Attitudes toward Rural Service in India : Results from Qualitative Research - Rao, Krishna D.; Ramani, Sudha; Murthy, Seema; Hazarika, Indrajit; Khandpur, Neha; Chokshi, Maulik; Khanna, Saujanya; Vujicic, Marko; Berman, Peter; Ryan, Mandy (World Bank, Washington, DC, 2013)
The paucity of qualified health workers in rural areas is a critical challenge for India's health sector. Although state governments have instituted several mechanisms, salary and non-salary, to attract health workers to rural areas, individually these mechanisms typically focus on single issues (e.g. salary). This qualitative study explores the career preferences of under-training and in-service doctors and nurses and identifies factors important to them to take up rural service. It then develops a framework for clustering these complex attributes into potential ?incentive packages for better rural recruitment and retention. The study was carried out in two geographically diverse Indian states, Uttarakhand and Andhra Pradesh. A total of 80 in-depth interviews were conducted with a variety of participants: medical students (undergraduate, postgraduate, and Indian system of medicine), nursing students, and doctors and nurses in primary health centers. The information collected was clustered by constructing several hierarchical displays, and collated into job-attribute matrixes. The findings indicate that, while financial and educational incentives attract doctors and nurses to rural postings, they do not make effective retention strategies. Frustration among rural health workers often stems from the lack of infrastructure, support staff, and drugs, a feeling exasperated by local political interference and lack of security.